Lipid nanoparticles for the delivery of biopharmaceuticals - Silva, Ana Catarina (2020)
Biopharmaceuticals comprise therapeutic protein-based, nucleic acids and cell-based products. According to their therapeutic success, the clinical use of these products has been growing. Therefore, the development of efficient biopharmaceuticals delivery systems, which overcome their limitations for administration, remains an excellent prospect for pharmaceutical technologists. In this area, lipid nanoparticles have been increasingly recognized as one of the most promising delivery systems, due to their exclusive advantages. However, no clinical biopharmaceutical lipid nanoparticle-based products are yet available. This fact could be explained by the lack or failure of in vivo studies, regarding stability and toxicological concerns, and also by the complex regulatory issues that must be accomplished. The present review article focuses on the different classes of biopharmaceuticals, their characteristics and limitations for administration. A state of the art regarding the use of lipid nanoparticles to improve biopharmaceuticals delivery is presented and a critical prospect of the future directions that should be addressed by pharmaceutical technologists is also discussed.